The generating function

Consider the function g(z)=\displaystyle e^{\alpha (z-1)} where \alpha is a positive constant. The following shows the derivatives of this function.

\displaystyle \begin{aligned}. \ \ \ \ \ \ &g(z)=e^{\alpha (z-1)} \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ g(0)=e^{-\alpha} \\&\text{ } \\&g'(z)=e^{\alpha (z-1)} \ \alpha \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ g'(0)=e^{-\alpha} \ \alpha \\&\text{ } \\&g^{(2)}(z)=e^{\alpha (z-1)} \ \alpha^2 \ \ \ \ \ \ \ \ \ \ \ \ \ \ g^{(2)}(0)=2! \ \frac{e^{-\alpha} \ \alpha^2}{2!} \\&\text{ } \\&g^{(3)}(z)=e^{\alpha (z-1)} \ \alpha^3 \ \ \ \ \ \ \ \ \ \ \ \ \ \ g^{(3)}(0)=3! \ \frac{e^{-\alpha} \ \alpha^3}{3!} \\&\text{ } \\&\ \ \ \ \ \ \ \ \cdots \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \cdots \\&\text{ } \\&g^{(n)}(z)=e^{\alpha (z-1)} \ \alpha^n \ \ \ \ \ \ \ \ \ \ \ \ \ \ g^{(n)}(0)=n! \ \frac{e^{-\alpha} \ \alpha^n}{n!} \end{aligned}

Note that the derivative of g(z) at each order is a multiple of a Poisson probability. Thus the Poisson distribution is coded by the function g(z)=\displaystyle e^{\alpha (z-1)}. Because of this reason, such a function is called a generating function (or probability generating function). This post discusses some basic facts about the generating function (gf) and its cousin, the moment generating function (mgf). One important characteristic is that these functions generate probabilities and moments. Another important characteristic is that there is a one-to-one correspondence between a probability distribution and its generating function and moment generating function, i.e. two random variables with different cumulative distribution functions cannot have the same gf or mgf. In some situations, this fact is useful in working with independent sum of random variables.

________________________________________________
The Generating Function
Suppose that X is a random variable that takes only nonegative integer values with the probability function given by

(1) \ \ \ \ \ \ P(X=j)=a_j, \ \ \ \ j=0,1,2,\cdots

The idea of the generating function is that we use a power series to capture the entire probability distribution. The following defines the generating function that is associated with the above sequence a_j, .

(2) \ \ \ \ \ \ g(z)=a_0+a_1 \ z+a_2 \ z^2+ \cdots=\sum \limits_{j=0}^\infty a_j \ z^j

Since the elements of the sequence a_j are probabilities, we can also call g(z) the generating function of the probability distribution defined by the sequence in (1). The generating function g(z) is defined wherever the power series converges. It is clear that at the minimum, the power series in (2) converges for \lvert z \lvert \le 1.

We discuss the following three properties of generating functions:

  1. The generating function completely determines the distribution.
  2. The moments of the distribution can be derived from the derivatives of the generating function.
  3. The generating function of a sum of independent random variables is the product of the individual generating functions.

The Poisson generating function at the beginning of the post is an example demonstrating property 1 (see Example 0 below for the derivation of the generating function). In some cases, the probability distribution of an independent sum can be deduced from the product of the individual generating functions. Some examples are given below.

________________________________________________
Generating Probabilities
We now discuss the property 1 indicated above. To see that g(z) generates the probabilities, let’s look at the derivatives of g(z):

\displaystyle \begin{aligned}(3) \ \ \ \ \ \ &g'(z)=a_1+2 a_2 \ z+3 a_3 \ z^2+\cdots=\sum \limits_{j=1}^\infty j a_j \ z^{j-1} \\&\text{ } \\&g^{(2)}(z)=2 a_2+6 a_3 \ z+ 12 a_4 \ z^2=\sum \limits_{j=2}^\infty j (j-1) a_j \ z^{j-2} \\&\text{ } \\&g^{(3)}(z)=6 a_3+ 24 a_4 \ z+60 a_5 \ z^2=\sum \limits_{j=3}^\infty j (j-1)(j-2) a_j \ z^{j-3} \\&\text{ } \\&\ \ \ \ \ \ \ \ \cdots \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \cdots \\&\text{ } \\&g^{(n)}(z)=\sum \limits_{j=n}^\infty j(j-1) \cdots (j-n+1) a_j \ z^{j-n}=\sum \limits_{j=n}^\infty \binom{j}{n} n! \ a_j \ z^{j-n} \end{aligned}

By letting z=0 above, all the terms vanishes except for the constant term. We have:

(4) \ \ \ \ \ \ g^{(n)}(0)=n! \ a_n=n! \ P(X=n)

Thus the generating function is a compact way of encoding the probability distribution. The probability distribution determines the generating function as seen in (2). On the other hand, (3) and (4) demonstrate that the generating function also determines the probability distribution.

________________________________________________
Generating Moments
The generating function also determines the moments (property 2 indicated above). For example, we have:

\displaystyle \begin{aligned}(5) \ \ \ \ \ \ &g'(1)=0 \ a_0+a_1+2 a_2+3 a_3+\cdots=\sum \limits_{j=0}^\infty j a_j=E(X) \\&\text{ } \\&g^{(2)}(1)=0 a_0 + 0 a_1+2 a_2+6 a_3+ 12 a_4+\cdots=\sum \limits_{j=0}^\infty j (j-1) a_j=E[X(X-1)] \\&\text{ } \\&E(X)=g'(1) \\&\text{ } \\&E(X^2)=g'(1)+g^{(2)}(1) \end{aligned}

Note that g^{(n)}(1)=E[X(X-1) \cdots (X-(n-1))]. Thus the higher moment E(X^n) can be expressed in terms of g^{(n)}(1) and g^{(k)}(1) where k<n.
________________________________________________
More General Definitions
Note that the definition in (2) can also be interpreted as the mathematical expectation of z^X, i.e., g(z)=E(z^X). This provides a way to define the generating function for random variables that may take on values outside of the nonnegative integers. The following is a more general definition of the generating function of the random variable X, which is defined for all z where the expectation exists.

(6) \ \ \ \ \ \ g(z)=E(z^X)

________________________________________________
The Generating Function of Independent Sum
Let X_1,X_2,\cdots,X_n be independent random variables with generating functions g_1,g_2,\cdots,g_n, respectively. Then the generating function of X_1+X_2+\cdots+X_n is given by the product g_1 \cdot g_2 \cdots g_n.

Let g(z) be the generating function of the independent sum X_1+X_2+\cdots+X_n. The following derives g(z). Note that the general form of generating function (6) is used.

\displaystyle \begin{aligned}(7) \ \ \ \ \ \ g(z)&=E(z^{X_1+\cdots+X_n}) \\&\text{ } \\&=E(z^{X_1} \cdots z^{X_n}) \\&\text{ } \\&=E(z^{X_1}) \cdots E(z^{X_n}) \\&\text{ } \\&=g_1(z) \cdots g_n(z) \end{aligned}

The probability distribution of a random variable is uniquely determined by its generating function. In particular, the generating function g(z) of the independent sum X_1+X_2+\cdots+X_n that is derived in (7) is unique. So if the generating function is of a particular distribution, we can deduce that the distribution of the sum must be of the same distribution. See the examples below.

________________________________________________
Example 0
In this example, we derive the generating function of the Poisson distribution. Based on the definition, we have:

\displaystyle \begin{aligned}. \ \ \ \ \ \ g(z)&=\sum \limits_{j=0}^\infty \frac{e^{-\alpha} \alpha^j}{j!} \ z^j \\&\text{ } \\&=\sum \limits_{j=0}^\infty \frac{e^{-\alpha} (\alpha z)^j}{j!}  \\&\text{ } \\&=\frac{e^{-\alpha}}{e^{- \alpha z}} \sum \limits_{j=0}^\infty \frac{e^{-\alpha z} (\alpha z)^j}{j!} \\&\text{ } \\&=e^{\alpha (z-1)} \end{aligned}

Example 1
Suppose that X_1,X_2,\cdots,X_n are independent random variables where each X_i has a Bernoulli distribution with probability of success p. Let q=1-p. The following is the generating function for each X_i.

. \ \ \ \ \ \ g(z)=q+p z

Then the generating function of the sum X=X_1+\cdots+X_n is g(z)^n=(q+p z)^n. The following is the binomial expansion:

\displaystyle \begin{aligned}(8) \ \ \ \ \ \ g(z)^n&=(q+p z)^n \\&\text{ } \\&=\sum \limits_{j=0}^n \binom{n}{j} q^{n-j} \ p^j \ z^j  \end{aligned}

By definition (2), the generating function of X=X_1+\cdots+X_n is:

(9) \ \ \ \ \ \ g(z)^n=\sum \limits_{j=0}^\infty P(X=j) \ z^j

Comparing (8) and (9), we have

\displaystyle (10) \ \ \ \ \ \ P(X=j)=\left\{\begin{matrix}\displaystyle \binom{n}{j} p^j \ q^{n-j}&\ 0 \le j \le n\\{0}&\ j>n \end{matrix}\right.

The probability distribution indicated by (8) and (10) is that of a binomial distribution. Since the probability distribution of a random variable is uniquely determined by its generating function, the independent sum of Bernoulli distributions must ave a Binomial distribution.

Example 2
Suppose that X_1,X_2,\cdots,X_n are independent and have Poisson distributions with parameters \alpha_1,\alpha_2,\cdots,\alpha_n, respectively. Then the independent sum X=X_1+\cdots+X_n has a Poisson distribution with parameter \alpha=\alpha_1+\cdots+\alpha_n.

Let g(z) be the generating function of X=X_1+\cdots+X_n. For each i, the generating function of X_i is g_i(z)=e^{\alpha_i (z-1)}. The key to the proof is that the product of the g_i has the same general form as the individual g_i.

\displaystyle \begin{aligned}(11) \ \ \ \ \ \ g(z)&=g_1(z) \cdots g_n(z) \\&\text{ } \\&=e^{\alpha_1 (z-1)} \cdots e^{\alpha_n (z-1)} \\&\text{ } \\&=e^{(\alpha_1+\cdots+\alpha_n)(z-1)} \end{aligned}

The generating function in (11) is that of a Poisson distribution with mean \alpha=\alpha_1+\cdots+\alpha_n. Since the generating function uniquely determines the distribution, we can deduce that the sum X=X_1+\cdots+X_n has a Poisson distribution with parameter \alpha=\alpha_1+\cdots+\alpha_n.

Example 3
In rolling a fair die, let X be the number shown on the up face. The associated generating function is:

\displaystyle. \ \ \ \ \ \ g(z)=\frac{1}{6}(z+z^2+z^3+z^4+z^5+z^6)=\frac{z(1-z^6)}{6(1-z)}

The generating function can be further reduced as:

\displaystyle \begin{aligned}. \ \ \ \ \ \ g(z)&=\frac{z(1-z^6)}{6(1-z)} \\&\text{ } \\&=\frac{z(1-z^3)(1+z^3)}{6(1-z)} \\&\text{ } \\&=\frac{z(1-z)(1+z+z^2)(1+z^3)}{6(1-z)} \\&\text{ } \\&=\frac{z(1+z+z^2)(1+z^3)}{6}  \end{aligned}

Suppose that we roll the fair dice 4 times. Let W be the sum of the 4 rolls. Then the generating function of Z is

\displaystyle. \ \ \ \ \ \  g(z)^4=\frac{z^4 (1+z^3)^4 (1+z+z^2)^4}{6^4}

The random variable W ranges from 4 to 24. Thus the probability function ranges from P(W=4) to P(W=24). To find these probabilities, we simply need to decode the generating function g(z)^4. For example, to find P(W=12), we need to find the coefficient of the term z^{12} in the polynomial g(z)^4. To help this decoding, we can expand two of the polynomials in g(z)^4.

\displaystyle \begin{aligned}. \ \ \ \ \ \ g(z)^4&=\frac{z^4 (1+z^3)^4 (1+z+z^2)^4}{6^4} \\&\text{ } \\&=\frac{z^4 \times A \times B}{6^4} \\&\text{ } \\&A=(1+z^3)^4=1+4z^3+6z^6+4z^9+z^{12} \\&\text{ } \\&B=(1+z+z^2)^4=1+4z+10z^2+16z^3+19z^4+16z^5+10z^6+4z^7+z^8  \end{aligned}

Based on the above polynomials, there are three ways of forming z^{12}. They are: (z^4 \times 1 \times z^8), (z^4 \times 4z^3 \times 16z^5), (z^4 \times 6z^6 \times 10z^2). Thus we have:

\displaystyle. \ \ \ \ \ \  P(W=12)=\frac{1}{6^4}(1+4 \times 16+6 \times 10)=\frac{125}{6^4}

To find the other probabilities, we can follow the same decoding process.

________________________________________________
Remark
The probability distribution of a random variable is uniquely determined by its generating function. This fundamental property is useful in determining the distribution of an independent sum. The generating function of the independent sum is simply the product of the individual generating functions. If the product is of a certain distributional form (as in Example 1 and Example 2), then we can deduce that the sum must be of the same distribution.

We can also decode the product of generating functions to obtain the probability function of the independent sum (as in Example 3). The method in Example 3 is quite tedious. But one advantage is that it is a “machine process”, a pretty fool proof process that can be performed mechanically.

The machine process is this: Code the individual probability distribution in a generating function g(z). Then raise it to n. After performing some manipulation to g(z)^n, decode the probabilities from g(z)^n.

As long as we can perform the algebraic manipulation carefully and correctly, this process will be sure to provide the probability distribution of an independent sum.

________________________________________________
The Moment Generating Function
The moment generating function of a random variable X is M_X(t)=E(e^{tX}) on all real numbers t for which the expected value exists. The moments can be computed more directly using an mgf. From the theory of mathematical analysis, it can be shown that if M_X(t) exists on some interval -a<t<a, then the derivatives of M_X(t) of all orders exist at t=0. Furthermore, it can be show that E(X^n)=M_X^{(n)}(0).

Suppose that g(z) is the generating function of a random variable. The following relates the generating function and the moment generating function.

\displaystyle \begin{aligned}. \ \ \ \ \ \ &M_X(t)=g(e^t) \\&\text{ } \\&g(z)=M_X(ln z)  \end{aligned}

________________________________________________

Reference

  1. Feller W. An Introduction to Probability Theory and Its Applications, Third Edition, John Wiley & Sons, New York, 1968
Advertisements

One thought on “The generating function

  1. thank you for the details for moment generating functions

    if you can add more about mgf (moment generating functions) such as their properties it’s may be very useful more than this

    thank you again

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s